The Länder and German federalism - Gunlicks, Arthur B., 1936- (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
This book provides a detailed introduction to how the Länder (the sixteen states of Germany) function not only within the country itself but also within the wider context of European political affairs. Some knowledge of the role of the Länder is essential.
Keywords: Federal government -- Germany.; Germany -- Politics and government -- 1990-; Society and social sciences.; Politics and government.; Regional government.; POLITICAL SCIENCE -- Civics & Citizenship.; POLITICAL SCIENCE -- Terrorism.; Federal government; Politics and government; Germany; Since 1990; Multi-User.